2019
DOI: 10.3390/tropicalmed4030115
|View full text |Cite
|
Sign up to set email alerts
|

Dog Owners’ Knowledge about Rabies and Other Factors That Influence Canine Anti-Rabies Vaccination in the Upper East Region of Ghana

Abstract: Background: Human rabies, often contracted through dog bites, is a serious but neglected public health problem in the tropics, including Ghana. Due to its high fatality rate, adequate knowledge and vaccination of domestic dogs against the disease are very crucial in reducing its burden. We examined dog owners’ knowledge level on rabies and factors that influenced anti-rabies vaccination of dogs in the Upper East Region of Ghana. Methods: This descriptive cross-sectional study was conducted among 260 randomly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 32 publications
5
27
0
Order By: Relevance
“…One of the major contrasts between the countries was found in the organization of dog vaccination campaigns. Ghana went from having national vaccination campaigns before 1997 to having to rely on more localized interventions dependent on local government and voluntary associations for financial and technical support after 1998 [ 39 , 43 , 44 ]. In India, the opposite was true, as local control programs were organized before implementing the NRCP and the ABC [ 76 ].…”
Section: Discussion: the Dynamics Of Intersectoral Collaborationsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major contrasts between the countries was found in the organization of dog vaccination campaigns. Ghana went from having national vaccination campaigns before 1997 to having to rely on more localized interventions dependent on local government and voluntary associations for financial and technical support after 1998 [ 39 , 43 , 44 ]. In India, the opposite was true, as local control programs were organized before implementing the NRCP and the ABC [ 76 ].…”
Section: Discussion: the Dynamics Of Intersectoral Collaborationsmentioning
confidence: 99%
“…Rabies in Ghana is endemic and was been identified as a neglected disease that posed a threat to public health due to many factors, including the large dog population, the weak surveillance system, and limited laboratory and vaccines supply [ [39] , [40] , [41] , [42] , [43] , [44] ]. Before 1998, the Government of Ghana conducted an annual national vaccination campaign led by the Veterinary Services Directorate and funded by the Ministry of Food and Agriculture.…”
Section: Overview Of Intersectoral Collaborations Under the One Health Approachmentioning
confidence: 99%
“…This result is in line with the study of Balan (2015) who revealed that majority of dog owners in Chennai were belonging to 19-35 years of age group, male and did graduation. Ameh et al, (2014), Awuni et al, (2019) and Baines et al, (2020), stated in their studies that majority of the pets were owned by male.…”
Section: Socio Economic Profile Of the Dog Owners In Chennaimentioning
confidence: 99%
“…Two studies reported an increase in MDV coverage following these activities [25,26], even though poor MDV coverage was also reported with the two other studies [27,28]. Mixed outcomes of awareness campaigns can be explained from Knowledge, Attitudes and Practices (KAP) studies showing that higher knowledge does not always translate into adoption of preventive measures [30][31][32][33]. Several studies reported misconceptions about appropriate preventive measures following a rabies exposure like a bite [30,[34][35][36].…”
Section: Outcome 11 Rabies Is Prevented Through Increased Awareness and Improved Educationmentioning
confidence: 99%